2019
DOI: 10.3904/kjim.2018.349
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning in rheumatic disease research

Abstract: Over the past decade, there has been a paradigm shift in how clinical data are collected, processed and utilized. Machine learning and artificial intelligence, fueled by breakthroughs in high-performance computing, data availability and algorithmic innovations, are paving the way to effective analyses of large, multi-dimensional collections of patient histories, laboratory results, treatments, and outcomes. In the new era of machine learning and predictive analytics, the impact on clinical decision-making in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 88 publications
(99 reference statements)
0
22
0
1
Order By: Relevance
“…In recent years, the use of machine-learning algorithms has gained popularity in healthcare due to their flexibility in handling large complex datasets and nonlinear relationships [ 8 , 9 ]. In addition, in the RA healthcare domain there are many opportunities for the application of machine-learning algorithms, for instance, the categorization of different arthritis subtypes or prediction of treatment response [ 10 , 11 , 12 ]. Others already successfully examined whether machine-learning algorithms could be used to predict response to MTX therapy in juvenile idiopathic arthritis (JIA) patients [ 13 ] and to antitumor necrosis factor in RA patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of machine-learning algorithms has gained popularity in healthcare due to their flexibility in handling large complex datasets and nonlinear relationships [ 8 , 9 ]. In addition, in the RA healthcare domain there are many opportunities for the application of machine-learning algorithms, for instance, the categorization of different arthritis subtypes or prediction of treatment response [ 10 , 11 , 12 ]. Others already successfully examined whether machine-learning algorithms could be used to predict response to MTX therapy in juvenile idiopathic arthritis (JIA) patients [ 13 ] and to antitumor necrosis factor in RA patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Between machine learning and traditional statistical methods, there are significant differences. First, machine learning focuses on the task of "forecasting", using universal learning algorithms to find patterns in variable and volumetric data [5]. In contrast, statistical methods are mainly focused on confirming hypotheses based on inferences, which are achieved by defining and approximating probability functions for a particular model [6].…”
Section: Methodsmentioning
confidence: 99%
“…For all of the supervised deep learning applications, data is the most critical factor in securing successful implementation and sustaining progress. Numerous studies have shown that access to data and data quality are crucial to enable successful machine learning of medical diagnosis, providing real assistance to physicians [3,4,5,6,7]. Exceptionally high-quality annotated data can improve deep learning detection results to great extent [8,9,10].…”
Section: Researchmentioning
confidence: 99%